On the use of interference suppression to reduce intermodulation distortion in multicarrier CDMA systems. - Weiping Xu (IEEE Transactions on communications)
This paper presents a coded multicarrier direct-sequence code-division multiple-access (DS-CDMA) system that, by the use of a minimum mean-squared-error receiver, achieves frequency diversity (instead of path diversity as in a conventional single-carrier RAKE DS-CDMA) and has the ability to suppress the intermodulation distortion and partially compensate for the signal distortion introduced by a nonlinear amplifier at the transmitter. A frequency-selective Rayleigh fading channel is decomposed into M frequency-nonselective channels, based on the channel coherence bandwidth. A rate 1/M convolutional code, after being interleaved, is used to modulate M different DS-CDMA waveforms. The new system is shown to effectively combat intermodulation distortion in the presence of multiple-access interference